Effects of nano-priming, priming time and post-priming maintenance on seed germination of sugar beet - Roozbeh, Faranak; Davoodi, Daryoush; Khayamym, Samar (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Background/Objectives: Recently reports on the effects of engineered nanomaterials on biological processes and plant growth are on the rise. In this study, the process of sugar beet seed germination under nanopriming treatments was investigated in compare to hydropriming. Methods/Statistical analysis: Seeds were treated under different concentrations of the nanomaterials, priming times, and post-priming maintenance. Kind of priming reagents with seven levels (water (hydropriming as control); 10, 20, 40 ppm nTiO2; and 10, 20, 40 ppm WNT), priming time with four levels (5 minutes, 6, 12, 18 hours), and post-priming seed maintenance with two levels (7 and 60 days) were considered as experimental treatments with three replications. Harvested data for variables root length, shoot length, fresh weight, dry weight, speed of germination, percent of germination, and seedling vigor were to undergo Multivariate and Univariate Analysis Of Variance by using SPSS software. Results: Nanopriming treatments produced same biomass but less root and shoot lengthscompared to hydropriming. According to mean comparisons, nanopriming could improve the sugar beet seed germination quality by increasing speed of germination, germination percentage and vigor of the seedlings significantly. Priming time and post-priming seed maintenance had also significant interactions with nanomaterials on the germination characteristics. Conclusion: With poorly adverse effects of post-priming storage on seed quality, seed priming with nanoparticles of titanium dioxide as compared to SWNT and hydropriming, caused a significant increase in the speed and percentage of germination